Privacy preserving using extended euclidean – algorithm applied to RSA - Nguyen, Thi-Nhung (Tạp chí Khoa học - Trường Đại học Sư phạm Hà Nội 2, 2023)
RSA cryptography is a strong encryption method widely used in online transactions. Using the extended Euclidean algorithm is an important and efficient technique for finding the secret key in RSA cryptography. This study provides an implementation of the extended Euclidean algorithm to find secret keys based on RSA cryptography and hopes that it can be of help to experts in the field of information security.